Innovation in university teaching. A proposal for interdisciplinary and collaborative work in higher education - Vargas D'Uniam, Jessica (2016)
This article presents the systematizing of the implementation of an experience of innovation in the university teaching realized from a perspective interdisciplinary and collaborative of the Faculty of Education and Faculty of Art, taking as an intention the creation of Peruvian stories for children for the development of the sensibility, the appraisal and valuation of the national and regional wealth. For the accomplishment of the analysis focal groups were used as method of compilation of information by the intention of knowing the perception of the students of the above mentioned powers on his participation in this formative activity. The process developed 22 children books with a Peruvians themes allowed each group of students to apply specialized knowledge and abilities learned within their respective faculties towards a common project which had a set of both pedagogical and artistic criteria.